Impact of Liquidity and Regulatory Capital on the Profitability of Nepalese Commercials Banks - Rijal, Ravi; Pradhan, Radhe Shyam (Nepalese Journal of Economics, 2024)
This study examines the impact of liquidity and regulatory capital on the profitability of Nepalese commercial banks. Return on assets and net interest margin are the dependent variables. The selected independent variables are current ratio, investment ratio, liquidity ratio, bank size, capital ratio and capital adequacy ratio. This study is based on secondary data gathered from 20 Nepalese commercial banks with 160 observations for the period from 2011/12 to 2018/19. The data are collected from Banking and Financial Statistics published by Nepal Rastra Bank and annual reports of the Nepalese commercial banks. The regression models are estimated to test the impact of liquidity and regulatory capital on the profitability of Nepalese commercial banks. The study showed that current ratio has a positive impact on return on assets and net interest margin. It indicates that increase in current ratio leads to increase in return on assets and net interest margin. Similarly, investment ratio has a positive impact on return on assets and net interest margin. It reveals that higher the investment ratio, higher would be the return on assets and net interest margin. However, liquidity ratio has a negative impact on return on assets and net interest margin. It means that higher the liquidity ratio, lower would be the return on assets and net interest margin. Similarly, bank size has a positive impact on return on assets and net interest margin. It reveals that larger the bank size, higher would be the return on assets and net interest margin. Likewise, the study also showed that bank capital ratio has a positive impact on return on assets and net interest margin. It indicates that higher the capital ratio, higher would be the return on assets and net interest margin. Similarly, capital adequacy ratio has a positive impact on return on assets. It reveals that higher the capital adequacy ratio, higher would be the return on assets and net interest margin.